Edukasi Bahaya Investasi Ilegal Dan Pinjaman Online Ilegal Di Deli Serdang Kecamatan Patumbak - Joharsah, Joharsah; Ikhwan, Hablil (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The rapid development of financial technology (fintech) in Indonesia has brought serious challenges, specifically the proliferation of illegal investment and online lending schemes that cause public unrest. This community service activity aims to provide education and improve financial literacy for residents in Patumbak District, Deli Serdang Regency, to prevent material and non-material losses resulting from illegal financial practices. The primary issue identified at the partner location was a low understanding of the legality of financial institutions and a lack of awareness regarding personal data protection, which is frequently exploited by illegal debt collectors through intimidating actions. The method employed in this service is a descriptive qualitative approach involving socialization stages, interactive discussions, and practical assistance based on the "Legal and Logical" (2L) principle. The effectiveness of the activity was measured through pre-test and post-test evaluations conducted with 35 participants. The results of the service demonstrate a significant increase in knowledge, with the participants' average score rising from 43.90 in the pre-test to 61.50 in the post-test. This improvement reflects that the community has begun to understand the importance of verifying permits from the Financial Services Authority (OJK) and maintaining the confidentiality of personal data. The success of this program was driven by the high enthusiasm of the participants and the full support of local village officials. In conclusion, direct and intensive education is effective in building the community's financial resilience at the district level against the threats of digital economic crimes.